Dampak Perceraian Orang Tua terhadap Kondisi Psikologis Anak: Systematic Literature Review - Sofa Aliyah Sita; St. Faza Yasyfa Jamal; Syakirah Ramadhani; Shabrina Nurul Wahidah Kosasih; Dian Novita Siswanti; Eka Sufartianinsih Jafar (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Parental divorce is a growing social phenomenon that may significantly impact children's psychological conditions. This study aims to analyze the impact of parental divorce on children's psychological condition, the forms of psychological problems experienced, and the influencing factors. The method used was a systematic literature review (SLR) of 30 scientific articles published between 2016-2026, sourced from the Google Scholar database, and meeting inclusion criteria such as having a DOI and relevance to family psychology topics. The review results indicate that parental divorce has multidimensional impacts, including: (1) emotional dysregulation and affective disorders (profound grief, anxiety, anger, trauma, and psychosomatic symptoms), (2) social maladaptation and externalizing behaviors (withdrawal, aggression, egocentric attitudes, and difficulty building interpersonal relationships), (3) decreased cognitive function and academic achievement (attention disorders, reduced learning motivation, and risk of dropping out of school), and (4) impaired self-acceptance, identity, and psychological well-being. These impacts are not deterministic but are moderated by risk factors (prolonged parental conflict, economic constraints, unstable parenting) and protective factors (social support, consistent parental communication, counseling interventions, and forgiveness skills). In conclusion, children's psychological condition after divorce is the result of a complex interaction between risk and protective factors, thus holistic interventions based on family, school, and community are essential to build children's resilience.